Katalogisasi Naskah Sunda Kuno Koleksi Kabuyutan Ciburuy - Mamat Ruhimat (Universitas Padjadjaran, 2017)
ABSTRAKTradisi tulis merupakan bukti kemajuan peradaban suatu bangsa. Naskah-naskahSunda Kuno yang ada saat ini merupakan peninggalan sejarah perjalanan bahasa dan budayaNusantara. Penelitian terhadap naskah-naskah Sunda Kuno tidak begitu banyak karenajumlah penelitinya sedikit. Bahkan katalog yang khusus mencatat naskah Sunda Kuno dimasyarakat pun belum ada. Katalogisasi Naskah Sunda Kuno di Jawa Barat merupakanupaya menginventarisasi dan mendokumentasi naskah-naskah Sunda Kuno di masyarakat.Katalogisasi juga merupakan direktori penelitian yang dilakukan terhadap naskah SundaKuno sehingga menjadi pembuka jalan bagi para peneliti yang ingin menggali kekayaanintelektual masa lalu. Katalogisasi naskah Sunda Kuno dimulai dari koleksi KabuyutanCiburuy di Kabupaten Garut. Kabuyutan ini menyimpan kurang lebih 30 kropak naskahSunda Kuno yang diperkirakan ditulis pada abad XVI-XVIII Masehi. Sebagian besar naskahlontar ini kondisinya rusak parah dan perlu penanganan yang serius. Dari ketiga puluhnaskah tersebut baru 15 naskah yang dapat diidentifikasi dan dibuat deskripsi lengkapnya.Kata kunci: Naskah, Katalog, Bahasa, BudayaABST RACTWritten tradition is evidence of the development of civilization of a nation. OldSundanese manuscripts still existing today is a historical heritage of linguistic and culturaljourneys of the Indonesian Archipelago. Unfortunately, most of the manuscripts are notappropriately preserved and from time to time continue to be damaged. Furthermore,the research on the Old Sundanese manuscripts is not so many due to the limited numberof the researchers. Even a catalogue especially listing Old Sundanese manuscripts in thesociety has not been made yet. The existing catalogues have only listed the manuscriptskept by the official institutions such as libraries and museums. Cataloging the OldSundanese manuscripts in West Java is one of the efforts to inventory and document theOld Sundanese manuscripts that are still scattered in the society, both stored in customaryinstitutions and personal collections. Cataloging is also a research directory that has everbeen conducted on Old Sundanese manuscripts, so it can be a pioneer for researchers whowant to explore the intellectual property in the past. As the first stage, cataloging theOld Sundanese manuscripts is started from the collection of Kabuyutan Ciburuy in GarutRegency. Kabuyutan stores approximately 30 compartments (kropak) of Old Sundanesemanuscripts that are estimated to have been written in the 16 to 18 century AD. Most ofthese manuscripts are badly damaged and need to be seriously taken care of. From thethirty manuscripts, only 15 manuscripts can be identified and can be completely described.Keywords: manuscript, catalogue, language, culture